2018
DOI: 10.3847/1538-4357/aada4e
|View full text |Cite
|
Sign up to set email alerts
|

Low-luminosity AGN and X-Ray Binary Populations in COSMOS Star-forming Galaxies

Abstract: We present an X-ray stacking analysis of ∼75,000 star-forming galaxies between 0.1 < z < 5.0 using the Chandra COSMOS Legacy survey to study the X-ray emission of low-luminosity active galactic nuclei (AGN) and its connection to host galaxy properties. The stacks at z < 0.9 have luminosity limits as low as 10 40 − 10 41 erg s −1 , a regime in which X-ray binaries (XRBs) can dominate the X-ray emission. Comparing the measured luminosities to established XRB scaling relations, we find that the redshift evolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 103 publications
5
42
0
Order By: Relevance
“…The measured evolution of L X (HMXB)/SFR ∝ (1+z) and L X (LMXB)/M ⋆ ∝ (1 + z) 2−3 out to z ≈ 2-4 Aird et al 2017) is only loosely constrained, but consistent with the population synthesis predictions from Fragos et al (2013a); however, see Fornasini et al (2018) for caveats. Extrapolation of the theoretical predictions into the very early Universe at z > ∼ 10, when the Universe was of very low metallicity ( < ∼ 1/10 Z ⊙ ; e.g., based on the Millenium II simulations; Guo et al 2011), indicate that XRBs were likely the most luminous X-ray emitting population in the Universe (e.g., Fragos et al 2013b;Lehmer et al 2016;Madau & Fragos 2017).…”
Section: Introductionsupporting
confidence: 73%
“…The measured evolution of L X (HMXB)/SFR ∝ (1+z) and L X (LMXB)/M ⋆ ∝ (1 + z) 2−3 out to z ≈ 2-4 Aird et al 2017) is only loosely constrained, but consistent with the population synthesis predictions from Fragos et al (2013a); however, see Fornasini et al (2018) for caveats. Extrapolation of the theoretical predictions into the very early Universe at z > ∼ 10, when the Universe was of very low metallicity ( < ∼ 1/10 Z ⊙ ; e.g., based on the Millenium II simulations; Guo et al 2011), indicate that XRBs were likely the most luminous X-ray emitting population in the Universe (e.g., Fragos et al 2013b;Lehmer et al 2016;Madau & Fragos 2017).…”
Section: Introductionsupporting
confidence: 73%
“…The L X /SFR of the z ∼ 2.3 stacks are higher than, but statistically consistent with, the z ∼ 1.5 stacks. The L X /SFR of the z ∼ 2.3 full sample stack is 2.3σ higher than the M12 value of 3.7 × 10 39 erg s −1 M ⊙ yr and 3.1σ higher than the L10 value of 1.6 × 10 39 erg s −1 M ⊙ yr. Fornasini et al (2018) find that for X-ray stacks with 50 galaxies such as these, L X may be biased to higher values than the true mean by 0.15 dex; 4 however, even accounting for this possible systematic effect, the z ∼ 2.3 stacks have enhanced L X /SFR compared to the L10 and M12 relations. Both the z ∼ 1.5 and z ∼ 2.3 full sample stacks are in good agreement with the L X /SFR values expected from the redshift evolution of the total X-ray binary (XRB) emission measured by Lehmer et al (2016) (shown by the dark gray long-dashed line in Figure 4; hereafter L16) and Aird et al (2017) (shown by the dark gray shortdashed line; hereafter A17).…”
Section: The Redshift Evolution Of Xrbsmentioning
confidence: 84%
“…Chen et al 2013;Hickox et al 2014;Lanzuisi et al 2017;Yang et al 2017). However, Yang et al (2017) show, via partial correlation (PCOR) analyses , that BHAR is actually more strongly related to host-galaxy total stellar mass (M ) than SFR (also see Fornasini et al 2018 for a similar conclusion). Their results suggest that the apparent BHAR-SFR relation is only a secondary effect resulting from a primary BHAR-M relation and the star formation main sequence.…”
Section: Introductionmentioning
confidence: 88%
“…As explained in Section 1, the BHAR quantity is designed to approximate long-term average SMBH accretion rate, and has been widely adopted in the studies of AGN-galaxy relations (e.g. Chen et al 2013;Hickox et al 2014;Yang et al 2017Yang et al , 2018aFornasini et al 2018). Some works proposed to recover the full distribution of BHAR as a function of galaxy properties (e.g.…”
Section: Black Hole Accretion Ratementioning
confidence: 99%